The EU supports a solution to the cotton crisis - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Speaking in Cancun on September 8th 2003, 'World Cotton Day', EU Trade...